The Human Resource Management in Improving The Quality of Educators at SMK Wahid Hasyim Glagah Lamongan - Abidah, Zakiyatul (Mudir : Jurnal Manajemen Pendidikan, 2024)
Abstract: Human resource management facilitates the actualization and competency development of educators and education personnel through systematic development and empowerment programs. The main objective of Human Resource Management is aimed at achieving the productivity of the organization concerned. It can be understood that all organizational activities in achieving its mission and goals depend on the humans who manage the organization. The Educational Institution of SMK Wahid Hasyim Glagah Lamongan is one of the educational institutions that is committed to advancing schools through educators who are competent in their fields. One of its efforts is through seminar programs, trainings, workshops, subject teacher deliberations, madrasah working groups and so on so that it is expected that human resources, namely educators, can work professionally and in accordance with organizational goals. This research methodology combines qualitative and descriptive approaches. Information is collected by means of observation, discussion, and documentation. The results of this study show that improving the quality of educators at SMK Wahid Hayim Glagah Lamongan is carried out in several stages, namely planning, recruitment of educators, selection, development and training, work assessment and compensation. The supporting factors of human resource management in improving the quality of human resources include support from the wider community and a conducive work environment. While the inhibiting factors of human resource management in improving the quality of educators include low teacher enthusiasm in providing new learning activity innovations. Keywords : Management Human Resources, Educators